Journal of Contemporary Private Law’s Presentation and General Editorial Guidelines - Rodrigues Junior, Otavio Luiz (Revista de Direito Civil Contemporâneo, 2020)
Journal of Contemporary Private Law’s Presentation and General Editorial Guidelines